Comparison of Antibacterial activity and medicinal properties of ginger (Zingiber officinale) and garlic (Allium sativum) between native and international genera - Karim, Mehnaz; Mosharraf, Fahareen Binta; Ahmed, Akash; Siddiqee, Mahbubul Hasan (British Journal of Healthcare and Medical Research, 2021)
Human societies have always a golden sign to show the noticeable spectacles of coexistence with their environments, precisely the impact of plants in every phases of their life. Several qualitative as well as quantitative approaches are taken into account to emphasize the effective integration of plants into a medical system. Therefore this experiment was designed to standardize and evaluate the health of active plant-extract and their dynamic use in healthcare system to open a new era in drug designing. In order to maintain this knowledge, plant extract of ginger and garlic from native and hybrid source were chosen (July 2018 to July 2019 from different zone of Bangladesh) in this experiment and sensitivity pattern of these extracts against two enteric disease causing organisms Bacillus cereus and Vibrio cholerae were conducted to investigate the role of these natural sources as medicinal plants. To compare the authenticity and efficacy of the plant extracts, selected strains were also challenged with conventional antibiotics. Finally, the results portrayed that the ethanoic and methanoic extract of both native garlic and ginger extracts showed more prominent sensitivity towards the gram negative organisms as compared to the foreign plants of same genera.